2010
DOI: 10.1093/qjmed/hcq132
|View full text |Cite
|
Sign up to set email alerts
|

Buying 'legal' recreational drugs does not mean that you are not breaking the law

Abstract: We have shown in this study that some drugs sold as 'legal' highs contain drugs that are controlled under the Misuse of Drugs Act (1971). Under current UK legislation, individuals purchasing legal highs that contained controlled drugs would be subject to the same penalties as if they had knowingly purchased a controlled drug. Dissemination of information on the harm associated with the use of legal highs should also inform individuals that they may be purchasing controlled substances and the potential legal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 9 publications
1
68
1
Order By: Relevance
“…It is possible that the Internet suppliers themselves may be confused as to which substance they are intending to sell, since in some user discussion fora, there appears to be confusion between 4-methylaminorex and 4,4′-dimethylaminorex [13,14]. In addition, there are numerous studies that have demonstrated that the contents of NPS products purchased from the Internet, high street headshops or street-level drug dealers are variable and the actual contents may not reflect the stated contents [15][16][17][18][19][20]. The main limitation of the Internet snapshot methodology is that the products are not purchased and analysed; therefore, it is not possible to be certain of the actual contents of the products being sold.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the Internet suppliers themselves may be confused as to which substance they are intending to sell, since in some user discussion fora, there appears to be confusion between 4-methylaminorex and 4,4′-dimethylaminorex [13,14]. In addition, there are numerous studies that have demonstrated that the contents of NPS products purchased from the Internet, high street headshops or street-level drug dealers are variable and the actual contents may not reflect the stated contents [15][16][17][18][19][20]. The main limitation of the Internet snapshot methodology is that the products are not purchased and analysed; therefore, it is not possible to be certain of the actual contents of the products being sold.…”
Section: Discussionmentioning
confidence: 99%
“…The true contents of the product can be obscured as advertising and packaging of these products is often misleading. "Bath salts" sold on websites reporting benign active ingredients, such as amino acids, phosphates, and magnesium salts, were found to contain synthetic cathinones [21]. Alternatively, other products advertised as containing synthetic cathinones as the active ingredients actually contained caffeine and local anesthetics [22].…”
Section: Contentsmentioning
confidence: 99%
“…As a consequence, drug users may have switched to mephedrone, as it was seen as cheaper and more powerful than the currently available 'traditional' stimulants (Deluca et al, 2009). Its availability over the Internet and its status as a 'legal high' (and therefore presumed not to be harmful) may have boosted its appeal (Daly, 2010;Ramsey et al, 2010).…”
mentioning
confidence: 99%